Chronic Kidney Disease Progression and Cardiovascular Outcomes Following Cardiac Catheterization—A Population‐Controlled Study. Issue 10 (October 2016) - Brown, Jeremiah R.; Solomon, Richard J.; Robey, R. Brooks; Plomondon, Meg E.; Maddox, Thomas M.; Marshall, Emily J.; Nichols, Elizabeth L.; Matheny, Michael E.; Tsai, Thomas T.; Rumsfeld, John S.; Lee, Richard E.; Sarnak, Mark J.
Abstract : Background: Studies of kidney disease associated with cardiac catheterization typically rely on billing records rather than laboratory data. We examined the associations between percutaneous coronary interventions, acute kidney injury, and chronic kidney disease progression using comprehensive Veterans Affairs clinical and laboratory databases. Methods and Results: Patients undergoing percutaneous coronary interventions between 2005 and 2010 (N=24 405) were identified in the Veterans Affairs Clinical Assessment, Reporting, and Tracking registry and examined for associated acute kidney injury and chronic kidney disease development or progression relative to 24 405 matched population controls. Secondary outcomes analyzed included dialysis, acute myocardial infarction, and mortality. The incidence of chronic kidney disease progression following percutaneous coronary interventions complicated by acute kidney injury, following uncomplicated coronary interventions, and in matched controls were 28.66, 11.15, and 6.81 per 100 person‐years, respectively. Percutaneous coronary intervention also increased the likelihood of chronic kidney disease progression in both the presence and absence of acute injury relative to controls in adjusted analyses (hazard ratio [HR], 5.02 [95% CI, 4.68–5.39]; and HR, 1.76 [95% CI, 1.70–1.86]). Among patients with estimated glomerular filtration rate <60 mL/min per 1.73 m 2, acute kidney injury increased the likelihood of disease progression by 8‐fold. Similar results were observed for all secondary outcomes. Conclusions: Acute kidney injury following percutaneous coronary intervention was associated with increased chronic kidney disease development and progression and mortality.